ACTIVITIES FOR OPENING TEACHING BY ENGLISH TEACHERS TO MOTIVATE STUDENTS IN THE CLASSROOM - Wijayadi, Kesuma (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
This study aims to find out the activities of opening teaching carried out by English teachers to motivate students in class VII of SMP Negeri 10 Padang. This type of research is qualitative with a descriptive method. Data collection techniques are carried out through interviews, observations, recording and recording. Based on the results of research and discussion of activities for opening teaching by English teacher to motivate students in class, it can be concluded that the skills of English teachers in grades VII at SMP Negeri 10 Padang in opening lessons include: (a) arousing students' attention, namely variations in teaching styles, use of instructional media and patterns of interaction (b) generate student motivation, namely excited and enthusiasm, generate curiosity, and generate conflicting ideas (c) provide references, namely convey learning objectives and determine activity steps (d) demonstrate linkages, namely determining stepping stones, generating new knowledge, providing continuous material. Related to all of these indicators, the researcher found that the activities for opening teaching by English teacher have been implemented although not all indicators and the results of the researcher found that the teacher motivated student learning for opening teaching activities by creating an active learning process such as making eye contact, providing discussion with question then students answer according to their knowledge, teacher character such as friendly, and explain the material with clear intonation.